Інформаційна безпека життєдіяльності людини і суспільства в умовах війни - Марченко, К. М.; Оришака, О. В.; Marchenko, К.; Oryshaka, О. (ЦНТУ, 2023)
У статті розглянуті аспекти інформаційної війни як невід'ємної складової гарячих війн. Проаналізовані механізми інформаційного впливу на свідомість людини та масову свідомість. Окреслені особливості інформаційної війни в умовах широкомасштабних військових дій в Україні. Наголошується, що інформаційна зброя приводить до сумірних наслідків із військовою зброєю та є різновидом зброї масового враження. Запропоновані інструменти та засоби протидії інформаційній агресії для людини та суспільства. The large-scale war started in Ukraine caused an intense surge of informational aggression and informational confrontation, the waves of which spread almost all over the world. Artificially prepared information is used as a weapon that works no less effectively than army weapons. The purpose of information weapons is primarily human consciousness and mass consciousness. Information security of human life and society in the conditions of intense information war becomes a priority task, as a guarantee of physical security. In the information war, which in the conditions of a flarge-scale military operations in Ukraine has become no less hot, new features and peculiarities are obvious: openness and frankness of information influences; the global nature of the information war; aggravation of information clashes, disputes, disputes; intensity of information attacks; attempts to disable military and infrastructure facilities by means of information; aggressiveness of information actions; informational violence; strict restrictions on access to information; politicization of information; significant polarization of information; an increase in the share of emotional coloring and subjective interpretation relative to the share of facts. Based on an overview of the scale of the informational impact on society and the destructive consequences, it can be argued that information is one of the weapons of mass impression. The best ways to counter informational influences and aggression are to provide true and comprehensive information; education of the population in the form of information security courses; individual trainings, especially for responsible persons; training of information security trainers; broad propaganda and development of information culture in the information society; media education - schools and information literacy courses for the population; learning the rules of information hygiene, prudence and legibility when contacting information. In particular, it is necessary to teach citizens critical thinking and recognition of negative informational influences, manipulation, misinformation, falsification, etc.
Information Security of Human Life and Society in Conditions of War
Keywords: інформаційна безпека; інформаційна війна; безпека життєдіяльності; свідомість; інформаційний вплив; інформаційна агресія; медіа-грамотність; іnformation security; information war; life safety; consciousness; information influence; information aggression; media literacy